Bound phenolics in rice bran dietary fibre released by different chemical hydrolysis methods: content, composition and antioxidant activities. (27th June 2022) - Zhao, Guanghe; Zhang, Ruifen; Dong, Lihong; Liu, Lei; Huang, Fei; Jia, Xuchao; Deng, Mei; Chi, Jianwei; Ma, Yongxuan; Chen, Yanxia; Ma, Qin; Zhang, Mingwei
Summary: Phenolics in whole grains naturally occur in free and bound forms, and are dominated by the latter. Previous study indicated that bound phenolics played an indispensable role in the health benefits of whole grain dietary fibre. However, existing extraction methods can only partly release bound phenolics, which results in an underestimation of their contents and activity. The content, composition and antioxidant activity of bound phenolics released from rice bran dietary fibre (RBDF) by different chemical hydrolysis methods were analysed in this study to explore a method releasing much more bound phenolics. The results showed that alkaline hydrolysis could release 1.54 times more phenolics than acid hydrolysis. The combination of 2 hydrolysis methods, especially alkaline‐acid hydrolysis (the residue after alkaline hydrolysis was then hydrolysed with acid), could more effectively release bound phenolics from RBDF. The 1, 1‐diphenyl‐2‐picrylhydrazyl (DPPH), oxygen radical absorbance capacity (ORAC) and ferric reducing antioxidant power (FRAP) antioxidant activity of the RBDF hydrolysates from different hydrolysis methods were generally consistent with their phenolic contents. However, the alkaline hydrolysate had 7.62% less phenolics, but showed 53.03% higher CAA activity than the acid‐alkaline hydrolysate. The RBDF residues after different chemical hydrolysis, furthermore, exhibited considerable DPPH and FRAP activity by QUENCHER method, indicating their possible local antioxidant activity in the colonic microenviroment. Abstract : Combining acid and alkaline hydrolysis released more bound phenolics from fibre. Four chemical hydrolysates of rice bran dietary fibre had different phenolic profiles. Unreleased bound phenolics in the hydrolysis residues showed antioxidant activity.